Effect of dietary supplemental black cumin seeds on antioxidant activity in broilers - Guler, Talat; Ertas, O. Nihat; Kizil, Meltem; Dalkilic, Bestami; Ciftci, Mehmet (My University, 2007)
The aim of this-study was to investigate the potential antioxidant activity of black cumin seeds as a dietary supplement. Three hundred 3-day-old broiler chicks were divided randomly into Ave treatment groups (control, and black cumin at four levels) of 60 birds each. Black cumin seeds at 0.5%, 1%, 2% or 3% were added to the basal diet and their effects determined on malondialdehyde (MDA) and vitamin E levels in the serum, breast muscles, liver and heart muscles in the 42-day old broilers. When the diet was supplemented with 2% and 3% black cumin seed MDA concentration in serum (p < 0.05), breast muscle (p < 0.01), liver (p < 0.05) and heart muscle (p < 0.05) was significantly more reduced compared to birds fed 1% and 0.5% black cumin seeds and control diet. Supplementing the diet with black cumin seeds did not significantly affect vitamin E levels in serum and tissues. These results suggest that black cumin seeds could be considered as a natural potential antioxidant promoter for poultry, and showed the best responses at 2% and 3% level of inclusion.
Keywords: Black cumin; Malondialdehyde